Urothelial Carcinoma Stage and Grade Association with the Expression Levels of Eukaryotic Initiation Factor 4E and 4E Binding Protein 1 - Mohammad Naji; Mahsa Yaghobinejad; Sepideh Mirzaei; Seyed Abdolhamid Angaji; Hajar Saber; Mahmoud Parvin; Farzaneh Sharifiaghdas (Middle East Journal of Cancer)
Background: Bladder cancer (BCa) accounts for the fourth most common cancer among men. Eukaryote translation initiation factor 4E (eIF4E) and its regulatory binding protein (4E-BP1) abnormal expression have been identified in numerous cancers. Therefore, we hypothesized and examined the existence of a connection between eIF4E and 4E-BP1 dysregulation and urothelial cancer (UC) in human subjects by employing more sensitive protein and gene expression experiments in both superficial and muscle-invasive UC.Method: In this case-control study, the eIF4E and 4E-BP1 mRNA and protein levels were assessed in snap-frozen tissue samples of normal (n = 23), superficial (n = 38) and muscle invasive (n = 29) UC by immunohistochemical staining, quantitative real-time polymerase chain reaction and western blot. A comparison of different groups was carried out by Mann–Whitney U and Kruskal–Wallis tests using Graph Pad prism version 9. P < 0.05 were considered as significant.Results: In addition to elevated expression for both eIF4E and 4E-BP1 in the UC group, we also considered upregulated patterns in both superficial and invasive UC as compared with the control group. An upregulated pattern was predominant in superficial group. Moreover, we observed diminished expression of eIF4E and 4E-BP1 in high-grade tissues of both superficial and invasive subjects compared with low-grade ones (P < 0.05).Conclusion: The present data indicates a possible link between decreased 4E-BP1 expression and high-grade UC that might be associated with expression of cancer promoting genes. Whilst eIF4E may play a role in low grade UC.